Three-Dimensional Morphometric Study of the Trapezium Shape of the Trochlea Tali - Rosdi, Daud; Mohammed Rafiq, Abdul Kadir; Sudin, Izman; Amir Putra, Md Saat; Muhammad Hisyam, Lee; Aminudin, Che Ahmad (Elsevier Ltd, 2013)
The trapezium shape of the talar dome limits the use of 2-dimensional plain radiography for morphometric assessment because only 2 of the 4 required parameters can be measured. We used computed tomography data to measure the 4 morphologic parameters of the trochlea tali: anterior width, posterior width, trochlea tali length, and angle of trapezium shape. A total of 99 subjects underwent computed tomography scanning, and the left and right talus bones were both virtually modeled in 3 dimensions. The 4 morphologic parameters were measured 3 times each to obtain the intraclass correlation, and analysis of variance was used to check for any significant differences between the repeated measurements. The average intraclass correlation coefficient for the measurements for 2 to 3 trials was 0.94 ± 0.04. Statistical analyses were performed on the data from all 198 talus bones using SAS software, comparing male and female and left and right bones. All 4 morphometric values were greater in the male group. No significant differences were found between the left and right talus bones. A strong positive correlation was observed between the trochlea tali length and the anterior width. The angle of trapezium shape showed no correlation with the other 3 parameters. The measurements were compared with the dimensions of the current talar components of 4 total ankle arthroplasty implants. However, most of them did not perfectly match the trapezium shape of the talus from our population. We successfully analyzed the trapezium shape of the trochlea tali using reliable virtual 3-dimensional measurements. Compared with other published reports, our study showed a relatively smaller dimension of the trochlea tali than the European counterparts.